Peningkatan Self Esteem Siswa melalui Layanan Bimbingan Kelompok dengan Teknik Sugesti - Putra, Hasta Purna (ISLAMIC COUNSELING: Jurnal Bimbingan Konseling Islam, 2017)
Parents attention and the general public attention toward children development tend to be more directed to cognitive aspect and psychomotor aspect. It is also suspected to occur to the educators and managers of educational institutions especially in the formal school. School as a place to prepare children to live better in the future presents the materials/subjects that emphasizes on the childrens cognitive development. In fact, to live does not merely depend on academic intelligence. Moreover, the emotional side of an individual can even hold a more dominant role than academic intelligence. In line with the schools objective to develop the students competencies from various aspects, it needs to realize that there are some psychological sides that should also be developed in the classroom learning process, such as self-control, achievement needs and mastership, and self esteem. Talking about self-esteem, almost all psychologists believe that it affects someones behavior which would also influence his presence in social environment. Self esteem is not formed solely from heredity, but is also influenced by the environment or the self system beyond. Generally, changing the behavior of students can be empowered by educational sectors, in which the guidance and counseling services are parts of the education. By providing guidance group service using the technique of suggestion can improve the students self esteem. The importance of the techniques of suggestion in guidance services need to be accompanied by a monitoring counselor in the school, so that it is really programmed to be able to increase the students self-esteem.